Study on Impulsive Buying Behavior among Consumers in Supermarket in Kathmandu Valley - Pradhan, Vidha (Journal of Business and Social Sciences Research, 2018)
This paper is an attempt to examine some of the factors affecting impulsive buying behavior of consumers in supermarkets. It also aims to verify the interrelationship between these factors and impulsive buying behavior. A primary research is carried out among people who shop in supermarkets in Kathmandu valley. A structured questionnaire is used to collect data from respondents of sample size 200. The sample is taken by convenience and quota sampling as per their age group. The findings suggest that majority of supermarket goers buy impulsively. Whenever they visit a supermarket, most of the respondents do not plan ahead. Instead, they scroll through aisles/products and buy what they think they need. Most of the respondents purchase certain products like personal care items, grocery and accessories impulsively. For other products like electronics and kitchenware, they take time to think if they really require those products. Taking into consideration each factor, product category has an insignificant role in influencing impulsive buying behavior. Similarly, respondents who have financial independence also have an insignificant role in influencing impulsive buying behavior. Among the factors that are significant for triggering impulsive buying behavior is availability of cash, mood of consumer, POS terminal/ATM facility, price, store layout, availability of time, product promotion, store environment and reference group. However, the same factors coupled with certain demographic variables may or may not have the same impact on impulsive buying behavior of the same consumers. Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 215-233